The Effects of Passenger Risk Perception During the COVID-19 Pandemic on Airline Industry: Evidence From the United States Stock Market - Lu, Zhou; Zhu, Linchuang; Li, Zhenhui; Liang, Xueping; Zhang, Yuan (Frontiers in Psychology, 2022)
The Covid-19 pandemic has caused a dramatic reshaping of passenger risk perception for airline industry. The sharp increase in risk aversion by air passenger has caused a disastrous impact on the tourism service industry, particularly airline industry. Although the existing literature has provided a lot of studies on the impact of the pandemic on travel industry, there are very few studies discussing the impact of change in passenger risk perception on the stock market performance of airline industry. This study considers two types of airline companies, full-service and low-cost. In order to overcome the traditional problem of the Chow test, Quandt-Andrews test is used to identify structural change points during the pandemic in the stock prices of U.S. airline companies. The result shows that an industry-wide structural change in the stock market performance indeed is found to take place during the pandemic for U.S. airline companies. Meanwhile, no significant difference is found in the structural change date between the two types of airline companies. The selected airline companies are found to be clustered towards the end of 2020 (November and December) in their structural change dates. Although the strike of the Covid-19 pandemic on airline industry has proven to be widespread and profound, our investigation implies that air passengers have gradually adapted to the new normal of travel activities at some level and partly rebuild their sense of safety under the strict epidemic-control measures.